2006
DOI: 10.1590/s1677-55382006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Paratesticular leiomyosarcoma treated by enucleation

Abstract: Spermatic cord leiomyosarcomas are rare tumors and standard treatment consists of radical orchiectomy and high cord ligation. We report a case of a paratesticular leiomyosarcoma successfully treated by enucleation. A 22-year-old man presented with a 6-months history of inguinal pain. Physical examination revealed a right paratesticular nodule about 0.5 cm in diameter. Inguinal exploration and nodule biopsy were performed. It was thought to be a benign epididymal nodule on a quick section and the tumor was enuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 4 publications
0
13
0
8
Order By: Relevance
“…Bu oranlar tüm genitoüriner tümörlerin %1-2'sini oluşturmaktadır. Leiomyosarkomlar paratestiküler sarkomların %10'unu oluşturmaktadırlar [4,5]. Bu tümörler üroloji pratiğin-de nadir görüldükleri için tanıda sıklıkla ilk planda düşünülme-mektedirler.…”
Section: Introductionunclassified
“…Bu oranlar tüm genitoüriner tümörlerin %1-2'sini oluşturmaktadır. Leiomyosarkomlar paratestiküler sarkomların %10'unu oluşturmaktadırlar [4,5]. Bu tümörler üroloji pratiğin-de nadir görüldükleri için tanıda sıklıkla ilk planda düşünülme-mektedirler.…”
Section: Introductionunclassified
“…The primary treatment with radical orchidectomy is an essential approach, but a single case report with local excision and surveillance has been reported. 5 A reported survival rate is 50%-80% and it has been observed that simple excision is suboptimal as repeat wide excision has demonstrated microscopic residual disease in 27% of cases and therefore warrants an additional adjuvant treatment. 6 A wide excision is almost mandatory if negative histological margins are not achieved during primary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the LMSs described in the literature are heterogeneous lesions like the aforementioned [6,11,15,16] although some LMSs appear to be hypoechoic [8,14] . Calcifications are not mentioned in the majority of the cases described [1,2,6,8,11,[14][15][16] . Colour Doppler ultrasonography shows either minimal [8] , or increased vascularity [11,16] .…”
Section: Discussionmentioning
confidence: 99%
“…The spermatic cord is the most common site of extratesticular neoplasia but only 30% of them are malignant, 90% of which are sarcomas. Approximately 10% of paratesticular sarcomas are LMSs [2] . This type of lesion is reported in all age groups but is mostly diagnosed in the 6th decade [3] .…”
Section: Introductionmentioning
confidence: 99%